A case of subclinical hypothyroidism with cerebellar ataxia - Shwet Sabnis; Tushar K Biswas (MGM Journal of Medical Sciences, 2022)
Hypothyroidism is a common condition, the symptoms and signs of which vary with the duration and magnitude of thyroid hormone deficiency. Hypothyroidism can have rare neurologic problems such as reversible cerebellar ataxia. Subclinical hypothyroidism refers to biochemical evidence of thyroid hormone deficiency in patients who have few or no apparent clinical features of hypothyroidism. Here, we present a case of a 70-year-old woman with complaints of giddiness and unsteadiness of 6 months’ duration. Subsequent evaluation revealed titubation, broad-based reeling gait, and dysarthria. A MRI of the brain showed diffuse moderate cerebral atrophy with periventricular ischemic white matter changes and normal cerebellum. Further investigations revealed evidence of subclinical hypothyroidism. The patient was started on oral thyroxine supplements with a relief of symptoms following 3 weeks after the initiation of treatment and a complete recovery from symptoms after about 3 months of the initiation of treatment. The association of cerebellar involvement at the stage of subclinical hypothyroidism is a rare finding, making the case academically interesting.